Developing content for an interprofessional training on fear of cancer recurrence (FCR): Key informant interviews of healthcare professionals, researchers and cancer survivors. Issue 3 (4th May 2018) - Berrett-Abebe, Julie; Cadet, Tamara; Vitello, Joan; Maramaldi, Peter
ABSTRACT: Background: Growing numbers of cancer survivors are receiving healthcare through primary care practitioners, who often lack cancer-specific expertise to effectively treat survivors' concerns. Addressing that gap, this study aimed to develop content for a training on fear of cancer recurrence (FCR), a common concern in survivorship. Methods: Grounded in naturalistic inquiry, 42 key-informant interviews were conducted, transcribed, and analyzed for themes. Participants were healthcare professionals, researchers, and cancer survivors Results: Results included themes ranging from: rich conceptualizations of FCR, opportunities and challenges for addressing FCR in healthcare settings, interventions to address FCR, and important information to include in a training on FCR. Conclusions: This paper provides content for an interprofessional training and highlights the importance of developing trainings for interprofessional teams, given identified barriers that physicians face in addressing FCR and other psychosocial concerns of survivors in primary care.